Synthesis and characterization of amorphous carbon nanotubes/copper oxide hybrid materials / Syazwan Hanani Meriam Suhaimy - Syazwan Hanani, Meriam Suhaimy (2012)
Carbon nanotubes (CNTs) are designated as one of the most attractive material from researchers due to their unique properties and, wider range of applications. However, the synthesizing process of crystalline CNT is still a great issue because of their synthesizing process involving complicated process such as need higher operating temperature, catalyst support and expensive production cost. On the other hand, the synthesizing process of amorphous,carbon nanotubes (α-CNTs) offer a simple process. This will facilitate the producing of CNTs and open new doors to many potential applications. Therefore, we reported in this work a way of preparing α-CNT and hybridizing it with Cu2O by a simple process using ferrocene and ammonium chloride at a low temperature (~250°C) in open atmosphere. The α-CNTs produced were purified with deionized for water and HCl for obtaining a high purity of CNTs. FESEM studies show that the morphology of the α-CNTs have changed after purification process. TEM studies revealed the diameter of the α-CNT and hybridized CNT. Raman studies revealed that the CNT is amorphous structure. EDX studies show the elements present in samples, and it is found that the major element is carbon. The X-ray diffraction pattern confirmed the amorphous nature of the sample and were also confirmed the presence of Cu2O. The band gap of untreated, treated and hybridized samples were confirmed with UV-Vis studies.